Los objetivos económicos de la micro y peque\~na empresa en México: Un análisis desde las elasticidades de factores productivos - Alejandro Mungaray Lagarda; José G. Aguilar Barceló; Germán Osorio Novela (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– A large body of economic literature has established that the primary purpose of business is profit maximization assuming unitary and constant elasticity of substitution of production factors. However, the prevailing operating conditions of micro and small enterprises raise concerns about the validity of this assumption and the objectives in this sector. Through an empirical study for Mexico and using the translog production function based on cross-sectional data by 2014, we find that the substitution elasticities between production factors are not unitary and even to some extent, they show complementarity. This forces us to consider that beyond seeking to maximize profits, micro and small enterprises might be including other objectives, such as to optimizing installed capacity.
Keywords: C31; C51; D20; D21; 330; elasticity; production factors; production functions; cost functions; maximization